2003
DOI: 10.1002/nag.268
|View full text |Cite
|
Sign up to set email alerts
|

Fast iterative solution of large undrained soil‐structure interaction problems

Abstract: SUMMARYIn view of rapid developments in iterative solvers, it is timely to re-examine the merits of using mixed formulation for incompressible problems. This paper presents extensive numerical studies to compare the accuracy of undrained solutions resulting from the standard displacement formulation with a penalty term and the two-field mixed formulation. The standard displacement and two-field mixed formulations are solved using both direct and iterative approaches to assess if it is cost-effective to achieve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…In this paper we focus on the standard displacement formulation (see, for example, [25]) and do not consider alternative methods such as mixed formulations (see, for example, [26]), which may be more effective for particular types of incompressible problems. For the displacement finite element method, the n × n (where n is the total number of degrees of freedom) structure stiffness matrix K in (1) is found by evaluating…”
Section: Finite Elements For Linear Elasticitymentioning
confidence: 99%
“…In this paper we focus on the standard displacement formulation (see, for example, [25]) and do not consider alternative methods such as mixed formulations (see, for example, [26]), which may be more effective for particular types of incompressible problems. For the displacement finite element method, the n × n (where n is the total number of degrees of freedom) structure stiffness matrix K in (1) is found by evaluating…”
Section: Finite Elements For Linear Elasticitymentioning
confidence: 99%
“…Physically, t → 0 produces the 'undrained' problem, whereas t →∞ produces the 'drained' problem. The former and latter problems (symmetric form) were studied in some details by Phoon et al [11] and Lee et al [12].…”
Section: Effect Of Non-symmetrymentioning
confidence: 99%
“…The generalized Jacobi (GJ) preconditioner developed by Phoon et al . has been shown to be effective in mitigating the ill‐conditioning because of low permeability in Biot's consolidation equations . Observing the breakdown of conventional symmetric successive over‐relaxation (SSOR) preconditioner for consolidation problems, Chen et al .…”
Section: Introductionmentioning
confidence: 99%
“…The generalized Jacobi (GJ) preconditioner developed by Phoon et al [6] has been shown to be effective in mitigating the ill-conditioning because of low permeability in Biot's consolidation equations [16][17][18][19]. Observing the breakdown of conventional symmetric successive over-relaxation (SSOR) preconditioner for consolidation problems, Chen et al [7] proposed the modified SSOR (MSSOR) preconditioner with GJ as the main diagonal, which outperforms both the GJ and the block constrained preconditioners [12].…”
Section: Introductionmentioning
confidence: 99%